A mathematical tool for predicting thermal performance of natural draft biomass cookstoves and identification of a new operational parameter. (15th December 2015) - Kshirsagar, Milind P.; Kalamkar, Vilas R.
Abstract: The goal of the work was to develop a simple yet reliable and computationally inexpensive mathematical tool for the performance prediction of 'rocket' type natural draft direct combustion stoves with unshielded pot. The work included development of a novel heat and mass transfer model for natural draft biomass cookstoves and its integration with Excel ® spreadsheet to develop a user-friendly mathematical tool. The results from the mathematical tool were validated against the experimental data set from literature. A new operational parameter named 'Inlet area ratio' was identified, and its effects on the stove performance were investigated. It was concluded that this newly identified parameter has a considerable effect on the performance of a natural draft stove, and the findings are likely to change the future cookstove modeling and design approach. Highlights: A novel heat and mass transfer model for analysis of biomass cookstove performance. Integration of the model with the excel spreadsheet. Development of a user-friendly mathematical tool for stove designer. Validation of the mathematical tool using experimental data from the literature. Identification of a new operational parameter affecting stove performance.